The impact of macroeconomic and financial factors on the performance of the housing property market in South Africa - Kwangware, Debra (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
This study exammes the impact of macroeconomic and financial variables on the performance of the housing property market in South Africa using monthly data for the period January 1996 to June 2008. Orthogonalised and non-orthogonalised house price returns and real estate returns are utilised as proxies for the housing property market in separate models. Three main issues were empirically analysed in relation to the linkage between selected variables and the housing property market. The first aspect examined the relationship between selected macroeconomic and financial factors and property returns. Secondly, the study examined the influence that a unit shock to each variable has on property returns over a period of time. The third aspect focused on determining the proportion of property returns variation that results from changes in the macroeconomic and financial variables. VAR modelling was thus adopted to empirically analyse these three aspects. The results reveal that house price returns are influenced by most of the macroeconomic and financial variables used in this study. Specifically, the real effective exchange rate, interest rate spread and manufacturing production positively impact on house price returns while the domestic interest rate, the dividend yield and expected inflation have a negative effect. Furthermore, manufacturing production has a lagged effect on house price returns while the real effective exchange rate and domestic interest rate have a contemporaneous effect. Real estate returns are not influenced by most of the variables except for the domestic interest rate and dividend yield which have a negative effect.
Keywords: Microeconomics; Housing -- South Africa; Housing -- Prices -- South Africa; Real property -- South Africa; Interest rates -- South Africa; Foreign exchange rates -- South Africa